2004
DOI: 10.1111/j.1469-8137.2004.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, production and interspecific competition in Sphagnum: effects of temperature, nitrogen and sulphur treatments on a boreal mire

Abstract: Summary• Growth and production of Sphagnum balticum and interspecific competition between S. balticum and either Sphagnum lindbergii or transplanted Sphagnum papillosum , were studied in a 4-yr field experiment in a poor fen.• Temperature and influxes of nitrogen (N) and sulphur (S) were manipulated in a factorial design. The mean daily air temperature was increased by 3.6 ° C with glasshouse enclosures. Nitrogen loads were increased 15-fold and S loads seven-fold compared with the natural loads up to influxes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 66 publications
(121 reference statements)
6
86
0
Order By: Relevance
“…Ground-dwelling mosses were more sheltered by higher vascular plants and suffered from a reduction in light availability (e.g. Gunnarsson et al, 2004). Thus, shade-tolerant species may allocate more N into light-harvesting pigments (Evans, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Ground-dwelling mosses were more sheltered by higher vascular plants and suffered from a reduction in light availability (e.g. Gunnarsson et al, 2004). Thus, shade-tolerant species may allocate more N into light-harvesting pigments (Evans, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental warming of bog vegetation in North America showed strongly increased above-ground production of ericaceous shrubs, without directly affecting moss growth (Weltzin et al 2000). A Swedish warming experiment showed reduced Sphagnum production which was related to increased vascular plant biomass (Gunnarsson et al 2004). These studies in intact bog vegetation suggest that Sphagnum can gain competitive advantage from increases in atmospheric CO 2 and that the vascular plants benefit from increases in temperature.…”
Section: Long-term Effects Of Climate Change On Bog Vegetationmentioning
confidence: 99%
“…Experimental studies have been conducted to study the response of Sphagnum bog plant communities to components of global change. In these experiments temperature (Bridgham et al 1999;Weltzin et al 2000Weltzin et al , 2003Gunnarsson et al 2004), atmospheric CO 2 Heijmans et al 2001b), water level (Bridgham et al 1999;Weltzin et al 2000Weltzin et al , 2003 and N deposition Heijmans et al 2001b;Gunnarsson et al 2004;Limpens et al 2004) have been manipulated during three or four growing seasons. All these studies showed that the main response was a shift in the relative abundance of species.…”
Section: Introductionmentioning
confidence: 99%
“…2). For example, an increase in temperature lengthens the growing season and increases mineralization rates (Aerts et al 1992;Gunnarsson et al 2004), which favors vascular plants (Backéus 1985). The accompanying decrease in Sphagnum might be self-enforcing because the temperature switch becomes less effective; a smaller proportion of Sphagnum in the peat layer leads to warmer conditions in the rooting zone of vascular plants, which further lengthens the growing season of vascular plants.…”
Section: The Impact Of Future Climate Change On Bogsmentioning
confidence: 99%
“…An accompanying amplifying effect could be that this increasing vascular plant density generates higher nutrient availability because of the nutrient switch. The latter switch could also amplify increased nutrient availability via atmospheric deposition (Gunnarsson et al 2004). Moreover, at high atmospheric deposition rates, Sphagnum is not capable of intercepting all nutrients (Lamers et al 2000;Berendse et al 2001;Malmer et al 2003), meaning that nutrients will leach into the rooting zone of vascular plants (Aerts et al 1992).…”
Section: The Impact Of Future Climate Change On Bogsmentioning
confidence: 99%